Poldérisation et préservation des paysages côtiers Singapouriens - Claire Doussard (Projets de Paysage)
The article studies the impact of the massive land reclamation projects conducted by the State of Singapore on the coastal landscape and its islands during the second half of the 20th century. The transformations in the landscape were a response to the policies of urban growth and economic development of a strong government on a territory with limited space. However, the development process was sometimes conducted to the detriment of the natural heritage of the area. In the place of the mangroves and mud flats new industrial and commercial spaces have encroached on the sea; spaces which are needed for the economic growth of Singapore. The article questions to what extent the Singaporean territorial expansion is an expression of the discrepancy between the economic policies for economic development and the ecological management of the coast, as well as their impact on the landscape. It studies two concrete cases in neighbouring areas which illustrate the impacts of these policies on the landscape: the mangroves of Sungei Mandai and of Sungei Buloj which have been the object of opposing planning approaches during the last forty years. These two mangroves originally constituted a single landscape entity which was subsequently broken up by different urban policies. Sungei Buloh is an exemplary case of environmental conservation. The surface area of Sungei Mandai was reduced to give room to industrial and residential uses which could be developed on future areas of reclaimed land. These two cases correspond to models of coastal area transformations specific to Singapore, at a time when its government is envisaging new territorial development strategies which will once again transform these landscapes.